Priority Level of Emotional Experience in Halal Tourism: Based on Age Generation of Tourists - Octaviany, Vany; Satrya, I Dewa Gde (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2024)
Great Bandung is a popular tourism destination, offering a variety of attractions that follow Islamic prin-ciples. These attractions cater to diverse emotional experiences, which vary significantly among tourists of different age groups. Research on emotional experiences of tourists based on age in the context of halal tourism is still rare. Therefore, this study aimed to determine “priority level" and "dominance in religion” as well as consider using "top priority" and "the importance of religious influence on tourist emotional experiences based on age group, namely Baby Boomer, Generation X, Y (Millennials), and Z, in halal tour-ism. Analytic Hierarchy Process (AHP) was used as the data analysis method and AHP questionnaire sam-ple consisted of 100 tourists. The result showed that spiritual assurance was top priority for Baby Boomer, while religious dominance was the least significant. Furthermore, the highest priority level for Generation X tourists was religious acceptance, and the least important was religious dominance. For Generation Y tourists, the most important factor was joy and the least is spiritual assurance.